2008
DOI: 10.1186/1743-422x-5-139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the nucleotide sequence of the guinea pig cytomegalovirus (GPCMV) genome

Abstract: In this report we describe the genomic sequence of guinea pig cytomegalovirus (GPCMV) assembled from a tissue culture-derived bacterial artificial chromosome clone, plasmid clones of viral restriction fragments, and direct PCR sequencing of viral DNA. The GPCMV genome is 232,678 bp, excluding the terminal repeats, and has a GC content of 55%. A total of 105 open reading frames (ORFs) of > 100 amino acids with sequence and/or positional homology to other CMV ORFs were annotated. Positional and sequence homologs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 38 publications
(36 reference statements)
2
56
0
Order By: Relevance
“…Recently, a UL82 homolog encoded by guinea pig cytomegalovirus (GPCMV) was found to stimulate the transfection efficiency of GPCMV DNA and to complement replication of a HSV-1 VP16 mutant. These data support the fact that, like pp71, the GPCMV UL82 gene product is an activator of viral IE gene expression, although it remains to be shown whether this involves counteracting Daxx in a species-specific way (124,125). Other members of the herpesvirus family also harbor virion proteins that target PML-NBs after infection.…”
Section: Daxx Impairment By Virion Proteins: Overcoming the Species Bsupporting
confidence: 62%
“…Recently, a UL82 homolog encoded by guinea pig cytomegalovirus (GPCMV) was found to stimulate the transfection efficiency of GPCMV DNA and to complement replication of a HSV-1 VP16 mutant. These data support the fact that, like pp71, the GPCMV UL82 gene product is an activator of viral IE gene expression, although it remains to be shown whether this involves counteracting Daxx in a species-specific way (124,125). Other members of the herpesvirus family also harbor virion proteins that target PML-NBs after infection.…”
Section: Daxx Impairment By Virion Proteins: Overcoming the Species Bsupporting
confidence: 62%
“…The new ORFs Rh00.2, Rh94.1, Rh96.1, Rh228.1, and Rh231 are predicted for both RhCMV strains, whereas ORFs Rh163.1, Rh165.1, and Rh166.1 are conserved between RhCMV 68-1 and the ULb= region of the low-passage-number isolate RhCMV CNPRC as described previously (51). However, the total number of ORFs predicted by this method for either RhCMV strain was substantially higher than that for any other published CMV genome (HCMV [25], CCMV [19], mouse CMV [MCMV] [60], rat CMV [RCMV] [76], and guinea pig CMV [GPCMV] [37,67]). Moreover, this annotation predicted that eight ORFs were unique to RhCMV 68-1 (Rh09, Rh39, Rh61, Rh93, Rh94, Rh142.4, Rh153, and Rh220.1) and that four ORFs were unique to RhCMV 180.92 (Rh13.1, Rh106.1, Rh142.3, and Rh178.2).…”
Section: Resultsmentioning
confidence: 87%
“…A major drawback in GPCMV research has largely been overcome by the recent sequencing of the viral genome and the development of infectious bacterial artificial chromosome (BAC) clones of GPCMV (15,(26)(27)(28)(29). Manipulation of an infectious GPCMV BAC has allowed the preliminary study of some viral genes (1,(30)(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Manipulation of an infectious GPCMV BAC has allowed the preliminary study of some viral genes (1,(30)(31)(32)(33)(34)(35)(36). Analysis of the viral genome (15,29) indicated that GPCMV encodes homologs to the HCMV glycoproteins (gB, gH, gL, gM, gN, and gO) in genes colinear with the HCMV genome (designated GP55, GP75, GP115, GP100, GP73, and GP74, respectively). In HCMV, these six glycoproteins (gB, gH, gL, gM, gN, and gO) are required for fibroblast cell entry, and they form the glycoprotein complexes gCI (gB), gCII (gM/gN), and gcIII (gH/gL/gO) on the viral membrane (37)(38)(39).…”
mentioning
confidence: 99%
See 1 more Smart Citation